Did plate tectonics control the generic diversity of Jurassic brachiopods? One point of view - Ruban, Dmitry A. (Geologos, 2018)
Possible plate tectonic controls on faunal diversity dynamics have been discussed in the geological literature for around 50 years. The new model of plate tectonic processes is here linked to Jurassic generic diversity (simple α-diversity) of brachiopods. This comparison offers three observations, four hypotheses and three unresolved issues. Most importantly, changes in the global plate root mean square speed coincided with brachiopod diversity dynamics, which can be explained hypothetically by either environmental disturbance triggered by more active plate motion or activity of any process (such as eustasy) tied to plate tectonic mechanisms and with an impact on marine benthic communities. It is also established that global generic diversity dynamics of brachiopods during the Jurassic coincided with the regional picture as established for the Northern Caucasus and the Swiss Jura Alps; this coincidence is difficult to explain with regard to plate tectonics. These and other speculative considerations do not clarify the role of the plate tectonic factor in Jurassic generic diversity dynamics of brachiopods, and, thus, they indicate important issues for further research.